2019
DOI: 10.1371/journal.pone.0219060
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio evolution is an independent predictor of early progression of second-line nivolumab-treated patients with advanced non-small-cell lung cancers

Abstract: Introduction Although second-line immunotherapy obtained better outcomes than chemotherapy for patients with advanced non-small–cell lung cancers (NSCLCs), it is expensive and only a minority of patients seem to benefit, based on early tumor progression post-immunotherapy. Notable host inflammation, characterized by biomarkers (e.g. neutrophil-to-lymphocyte ratio (NLR])), prolongs overall survival (OS) of surgery-, chemotherapy- and immunotherapy-treated patients. To our knowledge, no previous stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…42 To our best information, to date, no study particularly addressed the prognostic significance of PNI in NSCLC patients treated with the standard CRT followed by durvalumab or other immunotherapeutics. Nevertheless, neutrophil to lymphocyte ratio which is another inflammation index has been addressed as a prognostic indicator in some limited studies, [43][44][45] and a meta-analysis. 46 Reputably, Jiang et al conducted a comprehensive meta-analysis literature search to assess the relationship between pretreatment neutrophil to lymphocyte ratio and OS or PFS in advanced-stage cancer patients treated with immunotherapy.The pooled results of this meta-analysis of 27 studies with 4647 patients unveiled that high pretreatment neutrophil to lymphocyte ratio was closely linked with significantly shorter OS (HR = 1.98; P < 0.001) and PFS (HR = 1.78; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…42 To our best information, to date, no study particularly addressed the prognostic significance of PNI in NSCLC patients treated with the standard CRT followed by durvalumab or other immunotherapeutics. Nevertheless, neutrophil to lymphocyte ratio which is another inflammation index has been addressed as a prognostic indicator in some limited studies, [43][44][45] and a meta-analysis. 46 Reputably, Jiang et al conducted a comprehensive meta-analysis literature search to assess the relationship between pretreatment neutrophil to lymphocyte ratio and OS or PFS in advanced-stage cancer patients treated with immunotherapy.The pooled results of this meta-analysis of 27 studies with 4647 patients unveiled that high pretreatment neutrophil to lymphocyte ratio was closely linked with significantly shorter OS (HR = 1.98; P < 0.001) and PFS (HR = 1.78; P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…A high LIPI value was indicated as an independent negative prognostic factor (HR 3.67, 95% CI 1.96–6.86; p < 0.0001) [ 33 ]. Several other inflammatory-related markers, such as the neutrophil to lymphocyte ratio (NLR), dNLR, LDH, interleukin 8, and indoleamine 2,3 dioxygenase activity were also found to be important [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We summarized the characteristics in Table 1. Of all included studies, five were performed in the United States (7,31,33,34,40), four in Japan (32,36,39,44), and the remaining eight studies were conducted in Switzerland (35), Canada (37), France (38,45), Bulgaria (41), China (42), Germany (43), and Italy (46), respectively. In terms of the ICIs used, 11 studies reported on nivolumab (7, 31-36, 39, 42, 45, 46), 2 studies reported on pembrolizumab (41,44), and the remaining 4 studies did not specify the type of ICIs (37,38,40,43).…”
Section: Characteristics Of Eligible Studies and Quality Assessmentmentioning
confidence: 99%